Tiny Killers: First Record of Rhabdocoel Flatworms Feeding on Water Flea Embryos - Nedim Tüzün; Nina Lemke; Yander L. Diez; Tom Artois; Marlies Monnens (Ecology and Evolution)
ABSTRACT Flatworms are increasingly recognised for their ecological significance and potential to disrupt local fauna, yet most research has focused on conspicuous, larger planarians. Smaller flatworms, or microturbellarians, are often top predators within meiofaunal food webs. Here, we report a novel interaction involving a rhabdocoel microturbellarian, Strongylostoma simplex simplex, preying on Daphnia water flea embryos. We identified the flatworm based on histological serial sections and recognised key diagnostic traits. In a laboratory experiment, we tested for survival and offspring production of Daphnia magna in the presence and absence of S. simplex simplex. Exposure to flatworms caused a drastic reduction in water flea fitness, indicated by the strongly reduced survival and offspring production in flatworm‐exposed D. magna. This finding corroborates our visual observations of egg predation by these flatworms and suggests a strong pressure on Daphnia population dynamics. This is particularly concerning for small or isolated water bodies, such as the water wells located in a cemetery in Berlin in which we documented this interaction, as this would increase the probability of encounters between flatworms and water fleas. As Daphnia play an essential role in regulating phytoplankton blooms and supporting higher trophic levels in freshwater ecosystems, understanding the ecological consequences of predatory flatworms is imperative.